The Physicochemical properties and in silico binding interaction with gyrase B of antibacterial compounds from aquous extract of Hibiscus sabdariffa L. - Diyah, Nuzul Wahyuning; Andini, Khairunnisa; Isnaeni (Camellia : Clinical, Pharmaceutical, Analytical and Pharmacy Community Journal, 2024)
Hibiscus sabdariffa L. (Hs) is recognized to have various pharmacological activities such as antibacterial, antiedema, anti-fungal, antihypertensive, anti-inflammatory, and antiviral. The aquous extract of Hs’ calyx which is rich in polyphenols and flavonoids displayed antibacterial activity against several bacteria so that the compounds are important to be developed further as antibacterial agents. This study aims to find out which compounds contained in the extract have the antibacterial potency based on in silico interaction with gyrase B. Physicochemical descriptors of ten compounds were evaluated before molecular docking study, and the docking simulation was executed with Autodocktools 1.5.6. The selected compounds based on Lipinski’s Rules and their lower DG0 were subjected to prediction of pharmacokinetic and toxicity (ADMET) using pKCSM online tool. The results gave five test compounds showed the higher binding affinity on gyrase B compared to quercetin which served as inhibitor of the enzyme. The glycosides displayed better scores due to the existence of more hydroxyl groups. The potential aglycones were myricetin and delphinidin. According to the ADMET parameters, the two compounds have the best profile where they were neither hepatotoxic nor carcinogenic and also safer due to the higher LD50. In conclusion, the myricetin and delphinidin generated better binding interaction than the ligand inhibitor of gyrase B which indicated that they have higher potential as antibacterial agents.